Ethnomathematical Exploration of Traditional Agricultural Tools in Hutamanik Village, Sumbul Regency - Padang, Devi Syafitri; Lubis, Mara Samin (Universitas Islam Negeri Raden Intan Lampung, 2023)
This study explores using traditional farming tools in an ethnomathematics context in Hutamanik Village, Sumbul District. The research method used is qualitative, with data collection techniques through observation, interviews, and documentation. The collected data were analyzed with an ethnomathematics approach. Ethnomathematics in traditional agricultural tools can help people maintain local wisdom and strengthen cultural identity. The results showed that conventional farming tools, such as a water drum, coffee mill, sharpener, saw, hoe, and sickle, were used. Cultural, economic, and geographic factors influence the use of these tools. These tools contain mathematical concepts like measurement, comparison, and geometry. An ethnomathematics approach can be applied in learning mathematics to motivate students to learn mathematics because they can see that mathematics is related to everyday life. For this reason, it is suggested that future researchers explore ethnomathematics in different contexts.